Análisis multicriterial para la óptima ubicación de switch en redes eléctricas de distribución radial - Vinueza Carrillo, Mario Divaldo (2017)
The present article establishes a mathematical optimization model to improve the system average interruption frequency index SAIFI, an indicator of reliability applied to the distribution systems. The objective is to maximize the continuity of electrical service in distribution circuits with a purely radial topology, based on an optimal multicriterial analysis for the location of reclosers. The study focuses on the implementation of an optimization model to be solved using the Algebraic Modeling System (GAMS) software, applying the entire nonlinear mixed programming, establishing the optimal location of protection elements in a distribution circuit of twelve bars taking like a case of study. The methodology describes the feasibility of locating protection devices optimally from the technical, economic and operability point of view, considered in the planning and design of the primary feeders; with the object to minimize interruptions of service and energy not supplied.